Aspirations for a mass political party in prewar imperial Japan: conflicting visions of national mobilization - Grover, Bruce; Moniz-Bandeira, Egas (Parties as governments in Eurasia, 1913-1991, 2022)
Amidst the rising militarism of the 1930s, the power of Japanese political parties declined. Yet, they managed to maintain a foothold on power, and the Imperial Rule Assistance Association (IRAA; Taisei yokusankai 大政翼賛会), established in 1940, never quite became a mass political party. The chapter discusses the ultimately frustrated aspirations for the creation of a mass political party in the Japan of the 1930s and the 1940s, focusing on the thought and action of two networks which facilitated the trajectory of the IRAA: The “Alliance for a New Japan” (Shin Nihon dōmei 新日本同盟), a group consisting of some of Japan's most important bureaucrats, and the writings of the magazine Ishin 維新 (“Restoration”), which brought together many reform-minded military officers. The chapter shows that, while they did not put the role of the parliament as such into question, the focus of these thinkers lay on representing the “will of the people” through the Diet beyond liberal party politics. This transformation among important networks envisioned a transformation beginning primarily with a preparation of the mentality of the people through though guidance. Despite the apparent anomaly of the Japanese case in the late 1930s and 1940s, the history of IRAA in Japan was, thus, firmly part of a global trend toward a reconstruction of political systems. The IRAA was in large part a culmination of efforts at social transformation to create a form of political integration of the nation beyond liberal democracy and yet, nevertheless, sought active participation from all segments of society.